Development of Turret Punch Cutting Tool Using Reverse Engineering Method - M. M., Noor; R., Daud; K., Kadirgama; M. R. M., Rejab; N. M. Zuki, N. M. (2008)
This paper presents the reverse engineering technique to develop turret punch cutting tool for Trumatic TC2020R FMC machine. Different shear angle being tested to investigate the cutting process and tool wear. Result shows that 12o cutting tool has the highest tools life with poor performance. Cutting tool with 4.5o to 6.5o shear angle obtains lower tool life and better performance compare with 12o shear angle. By increasing the shearing angle, it will reduce the stress on the tool.